IMPACT OF CURRENT AFGHANISTAN SITUATION ON AFGHAN REFUGEES SETTLED IN DISTRICT PESHAWAR, PAKISTAN - Syed Habib Shah; Qamruz Zaman; Nisar Ullah; Sofia; Sidra Nawaz; Waqas Khan; Danish Waseem (International Journal of Contemporary Issues in Social Sciences, 2024)
To study the effect of current Afghanistan situation on afghan refugees settled in district Peshawar, KP, a sample of 280 afghan refugees were selected on referral basis. The analysis was done with the help of descriptive statistics. The sample of afghan refugees was selected from two different settled localities of district Peshawar i.e. 162 refugees from Hayatabad while 118 afghan from city areas of Peshawar. Also, in afghan refugees, there was 180 male afghan refugees and 100 female afghan refugees in which 61.1percent of afghan i.e. (161 afghan refugees) found scared from the current situation of Afghanistan whereas 38.9 percent of afghan refugees found not scared with the current scenario. The mean age of afghan refugee found as 35.4 years. Also 171 i.e. 61.1% of afghan refugee residing in Peshawar are depressed while 109 afghan refugees i.e. 38.9 percent found not depressed. Most of the afghan refugees found with the opinion of not visit to Afghanistan after the formal formation of government. Also, more of are the respondents are not in favor of Taliban government in Afghanistan and supposed USA responsible for all this in Afghanistan while the afghan refugees settled are not happy with the Taliban government.